Różnice funkcjonalno-semantyczne służebnych komponentów orzeczenia imiennego i czasownikowego - Popowa, Larysa (Studia Rossica Posnaniensia, 2010)
In the article are considered service components of analytical predicates (nominal and verbal). Despite presence the general attributes (service role in structure of a predicate, incomplete meaning, expression of predicative values), these components carry out different functions and possess specialized values. Distinctions of these verbs are caused by degree of the nominative importance, position in clause, functional loading, character of typical values (phase and modal), syntagmatic features.